The small molecule fibroblast growth factor receptor inhibitor infigratinib exerts anti-inflammatory effects and remyelination in a model of multiple sclerosis - Rajendran, Ranjithkumar; Rajendran, Vinothkumar; Böttiger, Gregor; Stadelmann, Christine; Shirvanchi, Kian; von Au, Laureen; Bhushan, Sudhanshu; Wallendszus, Natascha; Schunin, Darja; Westbrock, Victor; Liebisch, Gerhard; Ergün, Süleyman; et al. (My University, 2023)
Background and Purpose: Fibroblast growth factors and receptors (FGFR) have been shown to modulate inflammation and neurodegeneration in multiple sclerosis (MS). The selective FGFR inhibitor infigratinib has been shown to be effective in cancer models. Here, we investigate the effects of infigratinib on prevention and suppression of first clinical episodes of myelin oligodendrocyte glycoprotein (MOG)35–55- induced experimental autoimmune encephalomyelitis (EAE) in mice. Experimental Approach: The FGFR inhibitor infigratinib was given over 10 days from the time of experimental autoimmune encephalomyelitis induction or the onset of symptoms. The effects of infigratinib on proliferation, cytotoxicity and FGFR signalling proteins were studied in lymphocyte cell lines and microglial cells. Key Results: Administration of infigratinib prevented by 40% and inhibited by 65% first clinical episodes of the induced experimental autoimmune encephalomyelitis. In the spinal cord, infiltration of lymphocytes and macrophages/microglia, destruction of myelin and axons were reduced by infigratinib. Infigratinib enhanced the maturation of oligodendrocytes and increased remyelination. In addition, infigratinib resulted in an increase of myelin proteins and a decrease in remyelination inhibitors. Further, lipids associated with neurodegeneration such as lysophosphatidylcholine and ceramide were decreased as were proliferation of T cells and microglial cells. Conclusion and Implications: This proof of concept study demonstrates the therapeutic potential of targeting FGFRs in a disease model of multiple sclerosis. Application of oral infigratinib resulted in anti-inflammatory and remyelinating effects. Thus, infigratinib may have the potential to slow disease progression or even to improve the disabling symptoms of multiple sclerosis.
Keywords: Experimental autoimmune encephalomyelitis; FGFR; infigratinib; multiple sclerosis; neuroinflammation; remyelination; ddc:610